Studi Perbandingan Kepuasan Pasien terhadap Mutu Pelayanan Keperawatan dan Faktor Determinan di Tiga Rumah Sakit - Reni Fitria (Universitas Batanghari Jambi, 2019)
Introduction: Patient Satisfaction Is Related To The Quality Of Hospital Services. Satisfaction Is One Indicator Of Whether Or Not A Service Is Good And One Of The Consequences Of Low Satisfaction Can Be Seen From The Number Of Patient Visits To A Local Hospital. The Purpose Of The Study Was To Determine The Differences In Patient Satisfaction With The Quality Of Nursing Services In Hospitals In The City Of Padang. Method: The Design Of This Study Using Comparative Studies Was Carried Out. The Sample In This Study Amounted To 150 People, With A Quota Sampling Technique. Results: Of The Three Hospitals Obtained For R Hospital, A Small Percentage (24%) Of 12 Respondents Said They Were Satisfied. Y Hospital Is Small (10%) 5 Respondents Said They Were Satisfied. A Small Hospital (10%) 5 Respondents Said They Were Satisfied. The Statistical Test Results Obtained P-Value = 0,000 <0,05 Ho Was Rejected, Then There Were Differences In Satisfaction With The Quality Of Nursing Services In The Three Hospitals In The City Of Padang. Discussion: It Is Expected That Nurses In Providing Nursing Services To Patients Will Be Improved From Five Dimensions: Tangible, Realibility, Responsiveness, Assurance, Empathy So That The Quality Of Hospital Services Also Increases